Malnutrition and HIV pediatric infection in West Africa - (:unkn) unknown (My University, 2016)
HIV-infected children in sub-Saharan Africa are exposed to high risk of malnutrition duringtheir life. However, data on the nutrition of HIV-infected children are still limited in West Africa.Thus, the main objective of this thesis is to better investigate the link between nutrition and HIVinfection among HIV-infected children in West Africa. More specifically, it is aimed to estimate theprevalence of malnutrition, to describe growth evolution after antiretroviral treatment initiation, andto assess proposed nutritional interventions to integrate to pediatric HIV care. The main results showa high prevalence of malnutrition among these children, around 50% before antiretroviral treatmentinitiation. This initiation had positive effects on growth evolution; all the more important whenantiretroviral treatment is early initiated. Weight deficiency is easier to recover than heightdeficiency, but a substantial part of children stay malnourished even after two years of treatment. Inaddition to antiretroviral treatment, nutritional support interventions are needed to fight againstmalnutrition among these children. Those assessed were efficient for acute malnourished children,but not for those with chronic malnutrition. Furthermore, growth could be a useful marker of HIVprogression. Integration of nutritional care into global pediatric HIV care is possible in West Africa,but further studies and advocacy work have to be developed to better adapt it.
Keywords: African Research